Combination Therapy With Lenvatinib and Radiofrequency Ablation for Patients With Intermediate-Stage Hepatocellular Carcinoma Beyond Up-To-Seven Criteria and Child–Pugh Class A Liver function: A Pilot Study - Wang, Feiqian; Numata, Kazushi; Komiyama, Satoshi; Miwa, Haruo; Sugimori, Kazuya; Ogushi, Katsuaki; Moriya, Satoshi; Nozaki, Akito; Chuma, Makoto; Ruan, Litao; Maeda, Shin (Frontiers in Oncology, 2022)
Background: The present study aimed to evaluate the efficacy and safety of combined lenvatinib (first-line systemic therapy) and radiofrequency ablation (RFA) therapy in patients with intermediate-stage hepatocellular carcinoma with beyond up-to-seven criteria and Child–Pugh Class A liver function (CP A B2-HCC). Methods: Twenty-two patients with CP A B2-HCC were enrolled in the study. The patients had no history of systemic treatment. For the initial lenvatinib administration in this study, all of the patients had an adequate course of treatment (no less than two weeks) and were administered the recommended dose. Of them, 13 were treated by means of lenvatinib monotherapy (monotherapy group), while the 9 patients with no contraindication to RFA operation and who had consented to RFA received lenvatinib plus RFA (combination group). The clinical outcomes that were considered to evaluate the treatments included tumor response, prognosis (recurrence and survivals), and possible adverse events (serum liver enzymes and clinically visible complications). Results: The combination group exhibited a higher object response rate (9/9, 100%) as best tumor response than the monotherapy group (10/13, 76.9%). Longer progression-free survival (PFS) (12.5 months) and overall survival (OS) (21.3) were demonstrated in the combination group than in the monotherapy group (PFS: 5.5 months; OS:17.1 months). The combination group achieved a higher PFS rate (1-year: 74.1%) and OS rate (2-year: 80%) than the monotherapy group (1-year PFS rate: 0%; 2-year OS rate: 25.6%; for PFS, p<0.001; for OS, p=0.022). The treatment strategy was the independent factor for PFS (HR: 18.22 for monotherapy, p =0.010), which was determined by Cox regression analysis, suggesting that a combination strategy may reduce tumor progression when compared to the use of lenvatinib alone. There were no statistically significant intergroup differences that were observed in terms of adverse events, with the exception of ALT elevation (p=0.007) in the combination group. Conclusion: Our newly proposed combination therapy may potentially be effective and safe for CP A B2-HCC beyond up-to-seven criteria. A larger scale, multicenter, prospective study is warranted to confirm our findings.